2005
DOI: 10.2135/cropsci2005.0363
|View full text |Cite
|
Sign up to set email alerts
|

AFLP Assessment of Genetic Diversity of Capsicum Genetic Resources in Guatemala

Abstract: The genetic diversity of 74 chili pepper accessions (Capsicum spp.) was evaluated with amplified fragment length polymorphisms (AFLPs). Thirty‐four accessions were collected from home gardens throughout the Department of Alta Verapaz, Guatemala. The remaining accessions were selected from the national ex situ germplasm collection representing the diversity of 12 other departments of Guatemala. Most of the accessions belong to Capsicum annuum L., both cultivated and semicultivated types. A few accessions of C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 14 publications
(8 reference statements)
0
31
0
2
Order By: Relevance
“…Several previous case studies at the community level in Mexico (Perales et al, 2000;Perales et al, 2005;Latournerie-Moreno et al, 2006;Brush and Perales, 2007;Bellón and Hellin, 2011;Tuxill et al, 2010) and elsewhere (Brush, 2004;Guzman et al, 2005;Bisht et al, 2007;Rana et al, 2007;Jarvis et al, 2008;Bezançon et al, 2009;FAO, 2010;Jackson et al, 2010;Mulumba et al, 2012;Zimmerer, 2013) have demonstrated the persistence of landraces for climatic, ecological, cultural or social reasons. This trend is reaffirmed by the data from Mexico's national effort for maize diversity recollection (CONABIO, 2014).…”
Section: Longitudinal Analysis On Maize Varieties In Yucatan 57mentioning
confidence: 96%
“…Several previous case studies at the community level in Mexico (Perales et al, 2000;Perales et al, 2005;Latournerie-Moreno et al, 2006;Brush and Perales, 2007;Bellón and Hellin, 2011;Tuxill et al, 2010) and elsewhere (Brush, 2004;Guzman et al, 2005;Bisht et al, 2007;Rana et al, 2007;Jarvis et al, 2008;Bezançon et al, 2009;FAO, 2010;Jackson et al, 2010;Mulumba et al, 2012;Zimmerer, 2013) have demonstrated the persistence of landraces for climatic, ecological, cultural or social reasons. This trend is reaffirmed by the data from Mexico's national effort for maize diversity recollection (CONABIO, 2014).…”
Section: Longitudinal Analysis On Maize Varieties In Yucatan 57mentioning
confidence: 96%
“…The characterization and the evaluation of the Capsicum domesticated species are particularly interesting for gene bank curators, since a wide variability, not yet fully known and exploited, is available in these species (Guzmán et al, 2005;Sudré et al, 2006;Ince et al, 2009). Despite the accuracy in estimating genetic divergence among accessions by molecular markers, knowledge of the phenotype given by morphological and agronomical descriptors is still important.…”
Section: Introductionmentioning
confidence: 99%
“…Otros estudios analizaron la diversidad genética de distintas especies del género Capsicum en zonas muy concretas. Por ejemplo, en el Departamento de Amazonas (Colombia) y en el Departamento de Alta Verapaz (Guatemala) (Toquica et al, 2003;Guzman et al, 2005). Sin embargo, la distribución de la variabilidad genética a nivel molecular dentro de C. chinense, C. frutescens, C. baccatum y C. pubescens no ha sido muy estudiada, al estar representada cada especie con un pequeño número de entradas.…”
Section: Aprovechamiento De La Variabilidad Genética Conservada En Lounclassified
“…They might be hybrids, gene flow could be occurring as these species live together in the lower Andean land region and interspecific crosses are highly viable (Pickersgill 1971;Walsh and Hoot 2001;Guzman et al 2005). Although C. chinense and C.…”
Section: Relationships Among Speciesmentioning
confidence: 99%
See 1 more Smart Citation